A Possible Novel Mechanism of Action of Genistein and Daidzein for Activating Thyroid Hormone Receptor-Mediated Transcription. (23rd April 2018) - Ariyani, Winda; Iwasaki, Toshiharu; Miyazaki, Wataru; Yu, Lu; Takeda, Shigeki; Koibuchi, Noriyuki
Abstract: Thyroid hormone receptors (TRs) are members of the nuclear receptor superfamily that regulate their target genes for controlling organ development and functional maintenance. Soybean isoflavones, especially genistein and daidzein, modulate various hormone-mediated pathways. However, their effects on TRs have not yet been extensively studied. In this study, the effects of these isoflavones on TR action were evaluated using transient transfection-based reporter gene assays and molecular docking studies. Genistein and daidzein augmented T3 -liganded TR-mediated transcription in a concentration-dependent manner. In the mammalian 2-hybrid study, these isoflavones augmented the recruitment of steroid receptor coactivator-1 and nuclear corepressor to liganded or unliganded TRs. Using a series of mutant TRs, we also showed that the activation function-2 domain of TRs was responsible for the augmentation by these isoflavones. CV-1 cells had expressed TRα, TRβ1, and ERα mRNAs. However, neither the overexpression nor the knocking down of ERα altered the augmentation of TR action by isoflavones, indicating that the effects of isoflavones are exerted through their direct action on TRs. In silico molecular docking studies showed that genistein and daidzein can directly bind to the TR-ligand-binding domain. These findings indicate that the augmentation of the TR-mediated transcription by genistein and daidzein is due to their direct binding to TR-ligand-binding domain to induce the recruitment of steroid receptor coactivator-1. Our study reports a novel mode of action of soybean isoflavones on TR function. The biological effects and the relevance of these isoflavones to human health may be partially attributable to the activation of thyroid hormone signaling.